GIS-Based Spatial Analysis of Public Service Equity for Secondary School Facility Planning in Padang City - Aina Pahri; Yurni Suasti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
The equitable distribution of educational facilities is essential for ensuring fair and quality access to education for all members of society. Spatial imbalances in facility distribution can create disparities in access, affecting learning opportunities and educational outcomes across administrative regions. This study analyzes distribution patterns and service coverage of educational facilities using a Geographic Information Systems (GIS)–based spatial approach. A quantitative design is employed, incorporating Nearest Neighbor Analysis to identify spatial distribution patterns, buffer analysis to assess service coverage, and spatial overlay between service areas and residential settlements to determine served and underserved zones. The findings show that educational facilities are spatially clustered in specific areas, indicating that current provision does not fully align with the principle of equitable service distribution. Coverage analysis further reveals that several residential areas fall outside the optimal service radius, highlighting significant spatial access gaps. These results demonstrate the effectiveness of GIS-based spatial analysis in identifying inequalities in facility distribution and evaluating educational service equity. Practically, the findings provide evidence-based guidance for policymakers to prioritize facility development in underserved areas and to design spatially targeted planning strategies that enhance equitable access to education.